Prevalence of Iron Deficiency Anemia in School Going Children at District Bannu Khyber Pakhtunkhwa, Pakistan - Sayab Khan, Muhammad Suleiman, Farman Ali, Bakht Biland Khan, Muhammad Kamil Khan, Wali Ullah, Kashif Aziz, Hamad Khalid, Muhammad Irshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The purpose of the current research was to determine how common iron deficiency anaemia was among school-age children. Methodology: A total 200 blood sample in EDTA tube from school going children (6-12 year old) was collected at district Bannu KPK and then transported to Pathology Lab for Complete blood count using hematology analyzer and also transported for microscopy to evaluate the morphology of Red blood cells. Result: Total 200 blood samples were subject to Pathology Lab. Male was 110 (55%) and female were 90(45%). Total IDA positive cases were 120/200 (60%). IDA can be divided into three types of anemia due to Hemoglobin. The following types can occur First Mild Anemia: 10-10.9gm/dl (41.66%), second Moderate Anemia: 7-9.9gm/dl (37.5%), third extreme Anemia :< 7gm/dl (20.83%). Practical Implications: In district Bannu, a large number of children at school age had anemia despite the fact that its symptoms were challenging to identify and diagnose, but pale skin was the most prevalent sign of anemia. Conclusion: From this study we concluded that in district Bannu school going children have 60% anemia. The pale color of the children decreases physiological growth, and physical and mental activity. The female had 42.5% anemia as compare to male i.e. 17.5%. Between age of 10 and 12 the anemia cases was found. Keywords: IDA, MCV, MCH, MCHC, Serum ferritin prevalence, Bannu, Khyber Pakhtunkhwa. Keywords: anaemia, iron, children, Hemoglobin, human health